"Catfishing, " cyberbullying, and coercion: An exploration of the risks associated with dating app use among rural sexual minority males. Issue 3 (3rd July 2019) - Lauckner, Carolyn; Truszczynski, Natalia; Lambert, Danielle; Kottamasu, Varsha; Meherally, Saher; Schipani-McLaughlin, Anne Marie; Taylor, Erica; Hansen, Nathan
Abstract: This qualitative study ( N = 20) examined the online and mobile dating app use of sexual minority males living in non-metropolitan areas. Many participants reported negative experiences while using dating sites or apps. Specifically, they discussed instances of deception or "catfishing, " discrimination, racism, harassment, and sexual coercion (often mentioned in the context of young, sexually inexperienced men). The results indicate that the use of dating apps could pose mental health risks due to such negative and traumatic experiences. Future research should explore the health and mental health impacts of dating app use in order to improve care and services for the sexual minority male population.